Measurement of Dynamic Properties of O-rings and Stability Threshold of Flexibly Supported Herringbone Grooved Aerodynamic Journal Bearings - Jun Tomioka (Japanese Society of Tribologists, 2008)
The purpose of this paper is to measure the non-linear dynamic properties of O-rings in wide frequency ranges including in the ultra-high-speed rotational regions and to calculate the stability threshold of herringbone grooved aerodynamic journal bearings with O-rings support. First, the Voigt model was used as a rheological model of the O-rings, and the spring and the damping coefficients were evaluated in a wide frequency range from 0.5 to 4 kHz. Then, the stability threshold of the herringbone grooved aerodynamic journal bearings supported by O-rings was calculated. In this calculation, the compressible Reynolds equation based on the Narrow Groove Theory was solved by the perturbation method. Finally, the theoretical results were compared with the experimental results. The calculated results had a good agreement with the experimental ones